Additional Impact of Employee Income and Community Culture on Employee Discipline - Muklir; Muhammad Hasyem; Tonnyro Putra Darmawan (Jurnal Transparansi Publik (JTP), 2025)
The Bener Meriah Regency Government issued Regent Regulation Number 14 of 2019 concerning Additional Employee Income (TPP) which is expected to improve employee performance, especially from the discipline aspect, even though TPP has been given, the level of employee discipline is still quite low so that researchers want to look at external aspects such as community culture towards employee discipline. This research is a descriptive qualitative research carried out at the Personnel Agency, Education and Training of Bener Meriah Regency considering its main duties and functions as a personnel coaching agency so that it is appropriate to be able to apply proper discipline in accordance with the regulations that have been stipulated in Government Regulation Number 53 of 2010 concerning Employee Discipline. The results of the study show that the provision of TPP is still not able to improve employee discipline as expected because there is no TPP payment system that is integrated between discipline, performance and the amount of TPP received by employees. In addition, community culture has a considerable role in disciplinary violations within the Office of the Personnel, Education and Training Agency of Bener Meriah Regency.